Environmental and economic performance of different maintenance strategies for a product subject to efficiency erosion - Lee, Wo Jae; Joung, Byung Gun; Sutherland, John W. (Journal of cleaner production, 2023)
Different products have different environmental impact profiles across their life cycle stages. As examples, the environmental burden of an IC-engine based automobile is dominated by the use stage, and a desktop computer is dominated by the materials processing stage. Product life extension through maintenance is often viewed as an environmental benefit in that it obviates the need for early product replacement with its associated environmental impacts. However, in some cases, a rapid rate of change in a product may mean that a poorly performing product (during use), from an environmental perspective, is replaced with a better performing product. If such is the case, an early product failure may be a net environmental benefit. The argument discussed indicates that different maintenance strategies will have different environmental and economic consequences. In this paper, to quantify and compare the environmental and economic performance of different maintenance strategies, a methodology is developed using time-varying efficiency erosion models. As a case study, the maintenance of an electric motor driving a pump is presented. Further, different maintenance strategies are compared in terms of environmental and economic performance. The proposed method can help select maintenance strategies in the manufacturing plant while optimizing environmental and economic performance. •Erosion in power efficiency leads to additional energy consumption and CO2 emissions.•Power efficiency erosion behaviors are mathematically modeled.•A case study is introduced to quantify the environmental and economic performance.•Predictive maintenance is seen to be the most cost-effective strategy.